The quality assessment of state audit of financial and economic activity budgetary institution - Кожушко, Ольга Вікторівна (Technology audit and production reserves, 2015)
In the paper it is marked the stakeholders in assessing the quality of auditing the financial and economic activities of budget institutions, which include budget entity to be audited, state auditors involved in the review and State Financial Inspection. It is determined the criteria of the quality of financial audits, which include: compliance with applicable law; qualifications matching the staffing; implementation of recommendations issued after the state audit of financial and economic activity of budgetary institutions; adequacy of legal, methodological, financial and technical support. It is developed the methodical approach to assessing the quality of the state audit of financial and economic activity of budgetary institutions. The difference of the proposed methodological approach is a gradual process of criteria selection of state audit of financial and economic activities and their sequential combination. The proposed approach will ultimately possible to determine deficiencies in state auditors and enhance their professionalism and promote the convergence of national audit services market with the international community